The Role of Principal Leadership in Improving the Work Ethic of Islamic Religious Education Teachers (Pai) at SD Muhammadiyah 2 Sidoarjo - Abdul Gafur (Proceedings of The ICECRS, 2021)
The teacher is the transformational media of all the knowledge needed by students. In addition, the role of teachers is very much needed especially in Islamic-based schools that always pay attention and prioritize students to continue their studies in college. To get closer and to build with high enthusiasm for the achievement of the priorities above, the researcher conducted research at second grade of Elementary School in Sidoarjo by knowing more about the leadership style of the principal in improving the work ethic of Islamic Education teachers. This study is entitled "The leadership role of school principals in improving the work ethic of Islamic Religious Education teachers at second grade of Elementary School in Sidoarjo". This research is a qualitative study, through a phenomenological approach that is a qualitative research approach rooted in philosophical and psychological and focuses on human life experiences (sociology) that produce descriptive data in the form of written or oral data from observable people's behavior. The form of research is descriptive qualitative research, namely research that describes an object relating to the problem conducted without Role, leadership, principals, teachers’ work ethicasking research variables.The results of research on the role of principals in improving the work ethic of teachers of Islamic Education are as follows: (1) as educators: principals must have the right strategy to improve the work ethic of teachers and professional educators. (2) as a manager at school: the task of the manager is to plan something that can improve the work ethic of the teachers of Islamic Education and the quality of education, in addition the manager also organizes educational resources that have not been organized in order to unite in implementing education and control the implementation of educational outcomes . (3) as a motivator: the principal has a very close relationship with various activities in the school, such as providing motivation and encouragement, so the teacher is more disciplined and has a work spirit.